Sentidos e significados para o se-movimentar na dança em cadeira de rodas - Rigo, Laís Cavalheiro (2016)
We come upon critical about to dance and doing dance through techniques or "nontechnical" based in the repetition and copying movements, studies that warn us to the necessity of theoretical insights to legitimize dance and to dance as an expression and communication. Thinking about Wheelchair Dance (DCR) as a manifestation of increasing dance in search of spaces beyond the standardization of movements and gestures, we traced as the central objective of this study was to establish relationships between the Theory of "Self - Move Human" with the DCR teaching. To do this, we long constitute theorists deepening about the Dance that originated notes on aspects inherent the theme, as expressiveness, sensitivity, perception, body and creativity. From this we outline of intervention possibilities for DCR teaching. We understand that they ought not to study, research, write about Dance, one consisting phenomenon of imperceptible variables, by following a predefined method, based on certain assumptions. We commit to develop a theoretical research, a reflection on Dance, incited to argue and write about this phenomenon, enabling new syntheses go to meet the sense and meaning from our study, of our work. We find, in the dialogic relationship movement, possibilities for "doing dance" of expressive and communicative way, taking into account the senses and meanings intertwined in the movement of the subject danceable.